Shouldn’t all academic journals use structured abstracts? A logical necessity and an unexpected relationship with AI - Codina, Lluís (Anuario ThinkEPI, 2024)
Discussion on the implicit order and the explicit order in the abstracts based on the recommendation of the ISO standard in this regard. Proposal of the need for structured summaries for academic journals. Brief presentation of the standard structured abstacts model and two alternative structured abstracts models.